Aplicação das ferramentas da qualidade e avaliação da qualidade de vida no trabalho no diagnóstico de causas de baixa produtividade em uma equipe de manutenção elétrica industrial - PAIVA, Leandro Ferreira (2020)
The present work had as objective the application of the quality tools in the diagnosis of low productivity causes referring to an industrial electrical maintenance team. Through data collection using brainstorming session with employees and surveying the history of productivity goals, which served as the basis for the formulation of a case study where it was possible to begin the process of problem diagnosis. Through the use of quality tools one can map every step of the process, identify problems and get to the root cause. After the result, the first improvement proposal was elaborated through an action plan using the 5W1H tool, which aimed to improve the maintenance service. After this first part of the study it was found that the main problem would be related to the people who perform this process, due to the poor organizational culture spread within the team, behaviors and attitudes would be responsible for the inefficiency of the process. Taking into account the previous result, the second part of this study was initiated, where a Quality of Work Life Assessment (QWL) was elaborated with the team of collaborators through an electronic questionnaire in order to verify which parameters influence In the team's QWL, it was available to the team for one week, then the results were analyzed and the graphs were summarized that summarize the current QWL situation of the studied team. Thus, it was possible to elaborate the second improvement proposal also applying the action plan 5W1H, which this time had the purpose of providing a managerial improvement and pointing out the sectors where managers should act to improve the QWL and the quality of the maintenance process.